Health literacy and palliative care : workshop summary - Alper, Joe (The National Academies Press, 2016)
"The Institute of Medicine Roundtable on Health Literacy convened a 1-day public workshop to explore the relationship between palliative care and health literacy, and the importance of health literate communication in providing high-quality delivery of palliative care. Health Literacy and Palliative Care summarizes the discussions that occurred throughout the workshop and highlights the key lessons presented, practical strategies, and the needs and opportunities for improving health literacy in the United States"--Publisher's description